Effect of Intensive Training Programme on the Knowledge and Practice of Infection control among Auxiliary staff in a Tertiary care Hospital of Rawalpindi - Khan, Nazish; Azam, Naila; Mahmood, Humaira; Iftikhar, Asma; Afzal, Amir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the impact of health education intervention in the auxiliary healthcare staff regarding infection control knowledge and practices.Study Design: Quasi-experimental study.Place and Duration of Study: Inpatient departments, Fauji Foundation Hospital Rawalpindi, from Aug to Sep 2020.Methodology: Study participants were working as the auxiliary staff at Inpatient departments of Fauji Foundation Hospital. Pre-test was carried out for baseline assessment of knowledge and practice of infection control. There was training session of 3 hours comprising of lecture, practical demonstration and hands-on training regarding WHO five steps of hand hygiene, safe disposal of sharps and use of PPEs. Effectiveness of training intervention was assessed after one month.Results: Mean knowledge score increased from 8.22 ± 2.83 to 12.43 ± 2.05 after the training (p